Critical dialogue method of ethics consultation: making clinical ethics facilitation visible and accessible - Delany, Clare (Journal of medical ethics, 2025)
In clinical ethics consultations, clinical ethicists bring moral reasoning to bear on concrete and complex clinical ethical problems by undertaking ethical deliberation in collaboration with others. The reasoning process involves identifying and clarifying ethical values which are at stake or contested, and guiding clinicians, and sometimes patients and families, to think through ethically justifiable and available courses of action in clinical situations. There is, however, ongoing discussion about the various methods ethicists use to do this ethical deliberation work. In this paper, we make visible and accessible seven steps of facilitation used in the critical dialogue method of ethics consultation. We describe how the facilitation techniques serve two overall purposes. First, to identify ethically justified responses to ethical questions. Second, to assist participants to gain greater moral clarity, understanding and confidence to respond to ethical challenges as independent moral agents. By describing in detail facilitation steps for clinical ethics consultation, we aim to advance the scholarship of ‘clinical ethics facilitation methods’ and to demystify the ethical deliberation work undertaken by clinical ethicists.